Managing Personal Mobility Devices (PMDs) on nonmotorized facilities. - Litman, Todd (My University, 2010)
The paper explores the appropriate way to manage nonmotorized facilities (sidewalks, bikelanes, paths and trails), taking into account the increasingly diverse range of potential activities and modes, including various mechanical Personal Mobility Devices (PMDs) such as scooters, bicycles, and segways. It examines various types of activities and modes that may use nonmotorized facilities, discusses potential conflicts among these uses, describes general principles for managing nonmotorized facility use, and describes appropriate planning, management and education strategies for minimizing problems.
Keywords: Individualverkehr; Fahrradverkehr; Fußgängerweg; Nutzungskonflikt; Handlungsempfehlung; Radweg; Nichtmotorisierter Verkehr